New unified scientific theory and biothermal wave motion in the human body system - S. K. Srivastava (Science Faculty of Chiang Mai University, 2020)
A new Unified Scientific Theory based on the order-disorder concepts of the author has been employed in order to study thermal aspects of the quantized energy particle Lifton of bio-radiation. The present study concerns the motion of thermal waves generated by Lifton in the human body system. Two sets of homogeneous second-order differential equations based on (i) the variation of the Lifton wave function ΨL(t, T) with respect to parameters t and T and (ii) the variation of Lifton temperature T with respect to time t have been developed. The first set of equations provide frequencies ω = (2π EL / t) and ωp = (2π EL / T) which correspond to bio-radiation damping and plasma frequency respectively. Interesting results have been found. The damping is along longitudinal modes, while the effects of plasma are along transverse mode. The possibility of liquid plasma is also discussed. The second set of differential equations is concerned with body to free vibration with damping. Here the damping vibration frequency is ω = 1 / t at which human elastic structure systems tend to oscillate. This is the case of underdamped, i.e., the variation of temperature T with respect to time t is oscillatory and not periodic. An equation λL = (ЄT / pL) QF describes the relationship between the Lifton wavelength λL and linear momentum pL. This is Lifton’s duality; a relationship between the quantized wave nature and particle nature of Lifton. This equation is very similar to the de Broglie duality relationship of photons: λph = h / p, where h is Planck’s constant. The motion of thermal waves in the human body controls the ageing process of life. Equation T = exp [log (1 / t)] is concerned with the ageing of the human life-death system, which describes that the body temperature T decays exponentially as ageing occurs. That is why low blood temperature affects the blood circulation in old age. Equation T = (π Eth t)-1 is associated with the end-point of ageing when the human body system attains death (an ordered state). The Quantum vibration of Lifton generates thermal current in the human body system.